Identification of a Pivotal Period in the Oral Feeding Progression of Preterm Infants - Fucile, Sandra; Phillips, Sarah; Bishop, Kelly; Jackson, Meagan; Yuzdepski, Taylor; Dow, Kimberly (American Journal of Perinatology, 2019)
Objective Preterm infants are at risk of encountering oral feeding difficulties which impede on the transition to independent oral feeds. The objective of this study was to identify a pivotal period where regressions are most likely to occur during their oral feeding progression.Study Design This is a retrospective study on 101 infants born <35 weeks' gestation. The sample was separated into two groups, infants who experienced a regression during their oral feeding progression and those who did not. A pivotal period was defined as a time frame where setbacks (a decrease in oral feed attempts by one) are most likely to occur at the start (1–2 oral feed attempts per day), middle (3–5 oral feed attempts per day), or end (6–8 oral feed attempts per day) of the oral feeding progression.Result Eighty-two percent of infants experienced setbacks; 45% of all setbacks occurred at the middle time frame (p = 0.03). Infants' degree of maturity and enteral tube feeding intolerances were associated with increased occurrence of setbacks (p = 0.04).Conclusion The midpoint in the oral feeding progression is a pivotal period where setbacks are most likely to occur. This time frame can be used by clinicians to evaluate oral-motor skills for earlier provision of interventions to reduce the occurrence of oral feeding difficulties in this high-risk population.
Keywords: prematurity; infants; sucking; bottle/breast feeding